Inverted Diamond-shaped Notched Substrate and Patch for High-frequency Interference on Ultra-wideband Antenna - Raed Abdulkareem Abdulhasan; Khairun Nidzam Ramli; Rozlan Alias; Lukman Audah; Abdul Rashid Omar Mumin (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Notches loaded on a patch antenna can affect significantly on ‎the antenna impedance matching. Therefore, notching technique is an efficient way to reduce ‎the electromagnetic interference with unwanted bands. In this paper, a ‎novel inverted diamond‏-‏shaped closed-end slot on a substrate and ‎vertex-fed printed hexagonal patch ultra‏-‏wideband antenna is proposed for high-frequency band rejection. This antenna is fed using ‎coplanar waveguide, and it is optimised by veering several patch ‎parameters which further improved the inter bandwidth at both the ‎lower and upper bands. However, the centre-notched band is shifted ‎from 6 GHz to 7.5 GHz by cutting the inverted diamond shape in a ‎special process. The developed ultra-wideband antenna is verified by ‎comparing the simulation results with the measurement results. The ‎measured results with a fractional bandwidth of 133% have a good ‎agreement with the simulation results 146%. Moreover, the measured radiation showed omnidirectional patterns‎.